2013
DOI: 10.3855/jidc.2309
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of antibodies (IgG) to Taenia solium among pig rearers and associated risk factors in Jos metropolis, Nigeria

Abstract: Introduction: In Nigeria, Taenia solium cysticercosis is a problem in rural areas where most pigs are kept and in urban areas where infected pork can be consumed. Methodology: We performed enzyme linked immunosorbent assays on serum samples collected from pig rearers in Jos, Nigeria, to determine the prevalence of IgG antibodies.Results: Of 125 subjects tested, 12 (9.6%) were positive for T. solium. Seroprevalence did not differ significantly (P>0.05) according to education, age, occupation, study location, ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 29 publications
0
24
0
5
Order By: Relevance
“…The prevalence of 14.3% (n = 300) obtained in this study is high compared to those reported elsewhere; 9.6%, 2.4%, and 1.3% reported in Jos [11], Togo, and Benin, respectively [15], but closer to the 16.3% (n = 544) reported in Mbulu community, Tanzania [16]. Other studies using similar antibody detecting techniques have reported prevalence of 7.4% in South Africa and 20.5% in Mozambique [6].…”
Section: Discussionmentioning
confidence: 39%
See 2 more Smart Citations
“…The prevalence of 14.3% (n = 300) obtained in this study is high compared to those reported elsewhere; 9.6%, 2.4%, and 1.3% reported in Jos [11], Togo, and Benin, respectively [15], but closer to the 16.3% (n = 544) reported in Mbulu community, Tanzania [16]. Other studies using similar antibody detecting techniques have reported prevalence of 7.4% in South Africa and 20.5% in Mozambique [6].…”
Section: Discussionmentioning
confidence: 39%
“…Both sexes are equally predisposed to infection; sex is not a risk factor. In contrast, however, some studies in Plateau Nigeria [11], Tanzania [7], and Guatemala [18] have reported significantly higher prevalence in females than in males. Another study in Vietnam, however, reported higher infection rates in males than in females [20].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Human cysticercosis from Nigeria was obtained from two studies [47,48] by using Ab ELISA with prevalence of cysticercosis ranging from 9.6 to 14.3% in a total of 425 individuals. There were five studies selected for epilepsy [43,44,51,70] with prevalence ranging from 4.3/1000 to 20.8/1000 in a total of 64,979 individuals for the epilepsy study.…”
Section: Human Cysticercosis Taeniasis and Epilepsy In West Africamentioning
confidence: 99%
“…Approximately 90% of the world's 50 million people with epilepsy live in resource-poor countries [3], and a linkage between epilepsy and NCC in countries endemic for T. solium is now accepted. It is estimated that people with cysticercosis have a 3.4 to 3.8-fold increased risk for developing epilepsy [4].…”
Section: Introductionmentioning
confidence: 99%